Developing Blueprint for Public Services Information System in the District of Indonesia using Enterprise Architecture Planning Method - Yuli Maulani; Sri Lestari (JOIV : International Journal on Informatics Visualization, 2020)
Local government agencies, namely districts as regional technical implementers, are inseparable from the obligation to implement information technology, or better known as e-government, to create cohesiveness. Information systems in the district support the implementation of daily activities by only taking into account current needs without regard to conformity with the vision and mission and future needs of the district. Districts need careful planning in the form of architecture to complete the direction of the subdistrict strategy. This study aims to create a blueprint for developing information systems using the Enterprise Architecture Planning (EAP) methodology. Blueprint is designed to produce four main activities in the district, namely planning, government administration, integrated services, and governance with ten recommendations for cloud server-based applications, 5 of which use mobile platforms. The application has been mapped in the application portfolio to provide recommendations for implementing the application as a reference, clear guidelines, and plans for the development of the overall information system.